KEBUTUHAN BERTINGKAT TOKOH MERCY DALAM KKPK YOUNG SUPERSTAR KARYA KELLY LAURECIA HADI: KAJIAN PSIKOLOGI ABRAHAM MASLOW - Lestari, Adelia Putri (Universitas Negeri Surabaya, 2016)
KKPK is one medium of literature that is intended for children to have interesting reading material and quality, as well as age-appropriate. Children's literature through KKPK comes with a style that is easy to digest and simple conflict. This is because KKPK must conform to the world of children. In KKPK titled Young Superstar there needs major figure can be studied using the concept of need-rise property of Abraham Maslow, the fifth such needs include physiological needs, safety needs, needs love and affection, esteem needs or awards, as well as self-actualization needs.